Role of the calcium-binding protein parvalbumin in short-term synaptic plasticity - Caillard, Olivier (The National Academy of Sciences, 2000)
GABAergic (GABA = γ-aminobutyric acid) neurons from different brain regions contain high levels of parvalbumin, both in their soma and in their neurites. Parvalbumin is a slow Ca(2+) buffer that may affect the amplitude and time course of intracellular Ca(2+) transients in terminals after an action potential, and hence may regulate short-term synaptic plasticity. To test this possibility, we have applied paired-pulse stimulations (with 30- to 300-ms intervals) at GABAergic synapses between interneurons and Purkinje cells, both in wild-type (PV+/+) mice and in parvalbumin knockout (PV−/−) mice. We observed paired-pulse depression in PV+/+ mice, but paired-pulse facilitation in PV−/− mice. In paired recordings of connected interneuron-Purkinje cells, dialysis of the presynaptic interneuron with the slow Ca(2+) buffer EGTA (1 mM) rescues paired-pulse depression in PV−/− mice. These data show that parvalbumin potently modulates short-term synaptic plasticity.